The Effect of Health Education on Infusion of Patients on Maintenance of Infusion Drops at Citama Hospital in 2021 - Rogayah; Al-Bahra; Hernida Dwi Lestari (Unit Penelitian dan Pengabdian Masyarakat STIKES Fatmawati Jakarta, 2022)
This study aims to identify the characteristics of patients who are infusions, before and after infusion health education is carried out on patients for the maintenance of infusion drops at Citama Hospital in 2021. This study uses a Quasi Experimental method with the research design